2020
DOI: 10.1097/paf.0000000000000650
|View full text |Cite
|
Sign up to set email alerts
|

Nail Gun Suicide

Abstract: Nail guns are pneumatically driven or powder-actuated tools, which are used to drive nails into wood or concrete. A 42-year-old man, who was a builder by profession and history of antidepressant use, was found dead in his vehicle, holding a "Ramset" nail gun in his right hand. A straight metal nail and a book with a small hole were recovered from the scene.At autopsy, an irregularly circular puncture wound was seen on the forehead and a cruciate laceration was seen on the posterior aspect of the scalp. No burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(182 reference statements)
0
0
0
Order By: Relevance
“…A large number of published literatures favors conservative management of retained pulmonary foreign bodies in patients without symptoms [ 6 ]. One study showed that only 13% of patients with retained pulmonary parenchymal foreign bodies ultimately required surgical removal [ 7 ]. Once symptoms such as infection or bleeding occur, surgical excision or removal should be considered [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of published literatures favors conservative management of retained pulmonary foreign bodies in patients without symptoms [ 6 ]. One study showed that only 13% of patients with retained pulmonary parenchymal foreign bodies ultimately required surgical removal [ 7 ]. Once symptoms such as infection or bleeding occur, surgical excision or removal should be considered [ 8 ].…”
Section: Discussionmentioning
confidence: 99%